Chlorophyll a concentration of phytoplankton during a cruise of the 45th Japanese Antarctic Research Expedition in 2003-2004 - Hirawake, Toru; Iida, Masako; Matsuzaki, Masahiro; Kudou, Sakae; Fukuchi, Mitsuo (National Institute of Polar Research, 2006)
P(論文) departmental bulletin paper